Evaluation of Antifactor-Xa Heparin Assay and Activated Partial Thromboplastin Time Values in Patients on Therapeutic Continuous Infusion Unfractionated Heparin Therapy. (16th September 2019) - McLaughlin, Kevin; Rimsans, Jessica; Sylvester, Katelyn W.; Fanikos, John; Dorfman, David M.; Senna, Patricia; Connors, Jean M.; Goldhaber, Samuel Z.
Clinical uncertainty exists regarding which assay should be designated as the standard monitoring coagulation test for intravenous unfractionated heparin (UFH). Several studies have compared the use of activated partial thromboplastin time (aPTT) and antifactor-Xa (anti-Xa) and have come out with varying results. The correlation between these 2 tests varied, markedly from strong to weak. Some have demonstrated that monitoring with anti-Xa heparin assay leads to fewer dose adjustments, resulting in fewer laboratory tests, while others have not. In the current study, we evaluated the correlation between aPTT and anti-Xa values to guide clinical management of UFH, with the intention to develop a new correlation nomogram.